Structure, composition and electrochemical performance analysis of fluorophosphates from different synthetic methods: is really Na3V2(PO4)2F3 synthesized?. Issue 16 (22nd March 2022) - Li, Long; Zhao, Jing; Zhao, Hongyang; Qin, Yuanyuan; Zhu, Xiaolong; Wu, Hu; Song, Zhongxiao; Ding, Shujiang
Abstract : This work provides a reliable view for understanding the phase and composition of as-prepared Na3 V2 (PO4 )2 F3, showing that the proper introduction of oxygen substitution for fluorine is beneficial to the electrochemical performance. Abstract : Sodium vanadium fluorophosphate, Na3 V2 (PO4 )2 F3 (NVPF), has been confirmed to be a potential cathode material for commercial sodium-ion batteries, owing to its high operating voltage and super ionic conductivity. However, different charge/discharge potentials were reported in many "pure phase NVPF" research articles. In this work, we tried to clarify the misunderstandings about the NVPF composition and structure with comprehensive investigation by sol–gel, solid-state and hydrothermal methods. Relatively pure NVPF obtained by the solid-state method gradually decomposes into Na3 V2 (PO4 )3 above 600 °C. The sol–gel method would introduce O atoms into the F sites of the NVPF crystal structure, forming Na3 V2 (PO4 )2 F3− y O z and leading to a higher decomposition temperature. Na3 (VO)2 (PO4 )2 F single crystals produced by the hydrothermal method exhibit the best structural stability. Furthermore, the better crystallinity indicates higher specific capacity and cycle performances in all experiments. These novel findings reveal the relationship among F loss, structural changes, and electrochemical properties and provide a new understanding for the synthesis of NVPF cathodes.